Women in LOVe: Lacto-Ovo-Vegetarian Diet Rich in Omega-3 Improves Vasomotor Symptoms in Postmenopausal Women. An Exploratory Randomized Controlled Trial - Rotolo, Ornella; Zinzi, Iris; Veronese, Nicola; Cisternino, Anna M.; Reddavide, Rosa; Inguaggiato, Rosa; Leandro, Gioacchino; Notarnicola, Maria; Tutino, Valeria; De Nunzio, Valentina; De Leonardis, Giampiero; Guerra, Vito; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2019)
Objectives: In the postmenopausal period, most women suffer vasomotor symptoms (VMS). It is well-known that VMS can worsen the quality of life. Diet seems to play a relevant role in the development of VMS, but the effect of diet on VMS is mainly limited to observational studies, and analyses of nutritional supplements. The aim of this study was thus to determine the efficacy of a lactoovo- vegetarian (LOVe) diet rich in omega-3 fatty acids vs. a lacto-ovo-vegetarian diet rich in EVO (extra-virgin olive oil) in reducing VMS frequency in postmenopausal women. Methods: A two-arms (lacto-ovo-vegetarian diet with EVO vs. lacto-ovo-vegetarian diet rich in omega-3) randomized-controlled trial with a follow-up period of 16 weeks. We considered as primary outcome the change in the Kupperman index (follow-up vs. baseline evaluation, reported as delta, D) and in its subscales. Secondary outcomes included changes in common anthropometric and biohumoral measurements. Results: Among 54 women randomly assigned to a study group, 40 (mean age 55.1±5.4 years) completed the study and complied with their assigned diet. Women randomized to the omega-3 group (n=18) showed significant improvements, compared to the EVO group (n=22), in Kupperman index (Δ=-11.4±9.8 vs. -5.9±8.2; p=0.045), hot flashes (Δ=-3.3±3.4 vs. -1.3±2.6; p=0.04), and a marginally significant improvement in nervousness (Δ=-1.7±1.7 vs. -0.8±1.5; p=0.07). No significant differences were observed for the secondary outcomes. No relevant side effects were reported. Conclusion: After 16 weeks, a lacto-ovo-vegetarian diet rich in omega-3 reduced VMS frequency in postmenopausal women more than the lacto-ovo-vegetarian diet rich in EVO.
Keywords: lacto-ovo-vegetarian